丹戎布拉大学师范教育学院汉语教育专业 2017 届学生对 “程度副词 +有+名词” 句式的掌握分析 - Grasenda Bella Aprilia; Lily Thamrin; Tjen Veronica (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
The phrase structure of “程度副词+有+名词”is frequently used as the means of oral and written communication in human’s daily life. Due to the structure specialty in terms of its meaning and usage, many students might have encountered different types of problems. Thus, the structure of “程度副词+ 有+名词” is often considered as the one of the most difficult structures in Chinese grammar. The aim of this research is to investigate students’ mastery on “ 程度副词+ 有+名词” as well as their difficulties in using this structure.The research participants were the batch 2017 students in Chinese Language Study Program of Tanjungpura University. In order to achieve the research purpose, the researcher used library method and testing method for data collection. The research findings found that students’ average mastery in using “程度副词+有+名词” structure was 61.5%. Meanwhile, the researcher also found students’ difficulties in using the structure. The first one was the difficulty in differentiating “程度副词+有+名词”and “程度副 词+形容词” structures. The second one was the difficulty in finding the appropriate noun for the structure.